MOBILISATION TIMING AND INTENSITY AFTER ACUTE ISCHEMIC STROKE: BAYESIAN NETWORK META-ANALYSIS - Lunita, Angelina Ernestine Putri; Rumapea, Vivi Kristiani; Togatorop, Pascanus Lamsihar Parluhutan; Boy, Togu Deny; Sonya, Marta; Ekaputra, Anthony (MNJ (Malang Neurology Journal), 2026)
Background: Mobilisation after acute ischemic stroke is commonly practiced, yet the optimal timing and intensity remains uncertain. The AVERT trial (A Very Early Rehabilitation Trial) raised concerns regarding very-early and high-intensity mobilisation, but no prior synthesis has jointly compared timing–intensity strategies. Objective: To compare the effectiveness of mobilisation strategies classified by AVERT timing–intensity criteria and evaluate safety outcomes. Methods: We systematically searched through indexed search engines for randomised controlled trials. The primary outcome was favourable functional recovery at 90 days (modified Rankin Scale 0–2). Risk of bias was assessed using Cochrane RoB-2. A Bayesian random-effects network meta-analysis was performed with treatment ranking using surface under the cumulative ranking curve (SUCRA) and consistency assessed by node-splitting. Safety outcomes (complications and mortality) were summarised using direct comparisons with odds ratios (ORs) and forest plots. Results: Eight trials (n = 813) formed a connected network of six mobilisation strategies. Moderate-intensity mobilisation showed the highest probabilities of favourable outcomes across initiation timings. Also, early–moderate mobilisation was more favorable compared to delayed–moderate mobilisation (OR 2.14; 95% CrI 1.14–4.13). The Surface Under the Cumulative Ranking (SUCRA) curve placed moderate intensity strategies higher. Conclusion: Mobilisation delivered at a moderate intensity (3-6 sessions per day and 20-40 minutes/day) is associated with the highest probability of improved functional recovery at 90 days, when accompanied by careful monitoring and avoidance of very early and high-intensity mobility within the first 24-72 hours. Safety data were heterogeneous and needed standardised adverse-event reporting.